PRAKTIK RESTORATIVE JUSTICE GURU DALAM MENGELOLA KONFLIK ANTAR TEMAN SEBAYA DI SEKOLAH DASAR: BUKTI EMPIRIS DARI INDONESIA TIMUR - Lani Indriyani (STKIP Subang, 2026)
Peer conflicts in elementary schools negatively affect the school climate and student well-being, particularly in Eastern Indonesia where cultural complexity and institutional limitations exist. This study aims to explore teachers’ restorative justice practices in managing student conflicts, including conceptual understanding, mediation strategies, relationship-repair processes, and implementation challenges. The research used a qualitative approach with a single-case study design at SD Inpres 48, Sorong Regency. Data were collected through semi-structured in-depth interviews with one teacher and one student, classroom observation, and document analysis, then analyzed using Braun and Clarke’s thematic analysis model. The findings reveal three main results: first, the teacher holds a sound conceptual understanding of restorative justice as a restoration-based approach rather than a punitive one; second, the mediation strategies applied include emotion de-escalation, structured bilateral dialogue, development of mutual agreements, and post-conflict monitoring, which effectively repaired relationships among students; third, implementation barriers such as limited time, students’ lack of readiness to engage in dialogue, and parental resistance can be managed adaptively, while local cultural values like musyawarah (deliberation) and togetherness serve as facilitating factors. This study recommends developing restorative justice training that integrates local cultural values and systematically involves parents in elementary schools in Eastern Indonesia.